The part-time pay penalty in a segmented labor market - Daniel Fernández Kranz; Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2009)
While much of the literature that investigates the part-time (PT) / full-time (FT) hourly wage differential and its causes focuses on average effects, very few studies analyze the heterogeneous effects of PT work across different subgroups, despite the policy relevance of understanding channels behind the (raw) PT penalty in different labor markets. This paper is the first to examine the implications of switching to PT work for women's subsequent earnings trajectories, distinguishing by their type of contract: permanent or fixed-term. Using a 21-year unbalanced Social Security records panel of over 76,000 prime-aged women strongly attached to the Spanish labor market, we find that PT work aggravates the segmentation of the labor market insofar there is a PT pay penalty and this penalty is larger and more persistent in the case of women with fixed-term contracts. The paper discusses problems arising in empirical estimation, and how to address them. It concludes with policy implications relevant for Continental Europe and its dual structure of employment protection.
urn:nbn:de:101:1-20090909467
Keywords: J13; J16; J21; J22; J31; J62; C23; 330; Fixed-term and permanent contract; hourly wage levels and growth; prime-aged women; fixed-effects estimator; differential measurement error of HS variable; underlying channels; Lohndifferenzierung; Teilzeitarbeit; Arbeitsmarktsegmentierung; Schätzung; Spanien